Perancangan Aplikasi Signature Electronic Dengan Qr-Code Pada Pt. Sankyu Indonesia Internasional - Restutomo Herjiwandono, Bayu; Sukisno, Sukisno; Komalasari, Nia (Universitas Islam Syekh Yusuf Tangerang, 2024)
In the digital era, information technology is transforming various aspects of life, including education and business. Electronic Signature (eSign) have become a significant innovation in document verification and authentication, offering time efficiency and reduced administrative costs. PT. Sankyu Indonesia Internasional faces challenges in document management with manual Signature s, such as loss, damage, and forgery. To address this, an eSign application integrated with QR-Code was designed. This solution speeds up verification, reduces the risk of forgery, and enhances document Security. QR-Code assists in quick identification and information access. Combining eSign with QR-Code in a web application simplifies administration and document management at PT. Sankyu Indonesia Internasional, improving efficiency and Security, while protecting document integrity. This research aims to develop an eSign application with QR-Code specifically for PT. Sankyu Indonesia Internasional, enhancing efficiency, Security, and ease of information access in the company’s document management, and supporting the application of information technology within the company. Keywords: administration, e-sign, QR-Code, PT Sankyu